2014
DOI: 10.3892/mco.2014.478
|View full text |Cite
|
Sign up to set email alerts
|

High expression of pituitary tumor-transforming gene-1 predicts poor prognosis in clear cell renal cell carcinoma

Abstract: Abstract. Pituitary tumor-transforming gene-1 (PTTG1) is a recently identified oncogene involved in the progression of malignant tumors; however, the expression level of PTTG1 in clear cell renal cell carcinoma (ccRCC) and its potential value as a novel prognostic marker for ccRCC remains unclear. In this study, PTTG1 mRNA and protein levels were assessed in 44 paired ccRCC tissues and adjacent normal tissues by quantitative polymerase chain reaction (qPCR) and immunohistochemistry, respectively. Further immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…PTTG1 encodes Securin, a protein involved in the G2/M transition by inhibiting separation of sister chromatids 17 but also in DNA repair 18 and regulation of transcription. 19 It is a putative oncogene in a number of tissues such as the pituitary (where it was isolated) 20 and kidney 21 and was shown to be overexpressed in ACC by an independent study. 22 PRC1, also known as ASE1, encodes another key regulator of mitosis, which binds microtubules and is essential for the formation of the midzone bundle, central spindle organisation and subsequent cytokinesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTTG1 encodes Securin, a protein involved in the G2/M transition by inhibiting separation of sister chromatids 17 but also in DNA repair 18 and regulation of transcription. 19 It is a putative oncogene in a number of tissues such as the pituitary (where it was isolated) 20 and kidney 21 and was shown to be overexpressed in ACC by an independent study. 22 PRC1, also known as ASE1, encodes another key regulator of mitosis, which binds microtubules and is essential for the formation of the midzone bundle, central spindle organisation and subsequent cytokinesis.…”
Section: Resultsmentioning
confidence: 99%
“…PTTG1 encodes Securin, a protein involved in the G2/M transition by inhibiting separation of sister chromatids 17 but also in DNA repair 18 and regulation of transcription. 19 It is a putative oncogene in a number of tissues such as the pituitary (where it was isolated) 20 and kidney 21 and was shown to be overexpressed in ACC by an independent study. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies on genes in KIRC have mainly considered some known cancer-associated genes. For instance, Wei et al have found that high expression of pituitary tumor-transforming gene-1 ( PTTG1 ) in KIRC patients was associated with poor prognosis by using qRT-PCR and immunohistochemistry [ 27 ]. Peters et al have proved that low gene expression levels of GATA1 and GATA2 were related to tumor aggressiveness and short survival time in KIRC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 ccRCC has a poor prognosis with the metastatic rate of 15.3%-21.5% at presentation and a 5-year cancer-specific survival rate of 55%-82.7%, due to late stage and resistance to chemoradiotherapy. [35][36][37][38][39][40] Previously, some genes have been identified to correlate with tumorigenicity and prognosis of ccRCC; however, there were conflicting reports. Recently, numerous evidence has shown the central role of lncRNA in the regulation of cell proliferation, differentiation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%